Pengaruh Pendidikan Kewirausahaan, Literasi Digital, Efikasi Diri, dan Inovasi Terhadap Niat Berwirausaha - Nuraida, Nuraida (Indonesian Educational Administration and Leadership Journal (IDEAL), 2021)
The purpose of this study is to determine how students' entrepreneurial intentions are affected by the variables digital literacy, self-efficacy, innovation, and entrepreneurship education. The participants in this study were students at Jambi University. This location was chosen primarily for its entrepreneurial education. This study employs quantitative research techniques. A questionnaire was used to collect the data, and 200 Jambi University students responded. SEM-PLS, a data analysis tool based on Smart PLS version 3.2.9, was utilized in this study. The findings of the study demonstrate: 1) Entrepreneurial intention has no significant effect on entrepreneurial education; 2) Entrepreneurial intention has a significant effect on digital literacy; 3) Entrepreneurial intention has a significant effect on self-efficacy; 4) Innovation has no significant effect on entrepreneurial intention; 5) Innovation has a significant effect on Entrepreneurship Education; 6) Innovation has no significant effect on the self-efficacy of Jambi University students. As a result, it is possible to draw the conclusion that some of these variables have an effect on the entrepreneurial intentions of Jambi University students, while others have no effect at all. Kata Kunci : Education In Entrepreneurship, Entrepreneurial Intention, Self-Efficacy.